Investigating the accuracy of co-registered ionoacoustic and ultrasound images in pulsed proton beams. (9th September 2021) - Lascaud, Julie; Dash, Pratik; Wieser, Hans-Peter; Kalunga, Ronaldo; Würl, Matthias; Assmann, Walter; Parodi, Katia
Abstract: The sharp spatial and temporal dose gradients of pulsed ion beams result in an acoustic emission (ionoacoustics), which can be used to reconstruct the dose distribution from measurements at different positions. The accuracy of range verification from ionoacoustic images measured with an ultrasound linear array configuration is investigated both theoretically and experimentally for monoenergetic proton beams at energies relevant for pre-clinical studies (20 and 22 MeV). The influence of the linear sensor array arrangement (length up to 4 cm and number of elements from 5 to 200) and medium properties on the range estimation accuracy are assessed using time-reversal reconstruction. We show that for an ideal homogeneous case, the ionoacoustic images enable a range verification with a relative error lower than 0.1%, however, with limited lateral dose accuracy. Similar results were obtained experimentally by irradiating a water phantom and taking into account the spatial impulse response (geometry) of the acoustic detector during the reconstruction of pressures obtained by moving laterally a single-element transducer to mimic a linear array configuration. Finally, co-registered ionoacoustic and ultrasound images were investigated using silicone inserts immersed in the water phantom across the proton beam axis. By accounting for the sensor response and speed of sound variations (deduced from co-registration with ultrasound images) the accuracy is improved to a few tens of micrometers (relative error less than to 0.5%), confirming the promise of ongoing developments for ionoacoustic range verification in pre-clinical and clinical proton therapy applications.